Effect of Surface Pavement Type on Traffic Noise - Amjed J. Abed; Amjad H. Albayati; Yu Wang (Journal of Engineering, 2023)
This paper investigates the issue of surface-type effects on traffic noise in Baghdad. Since the raw materials for both flexible and rigid paving are available from local sources, the decision on selecting the type of paving which depends on the budget of the project and the road's importance and function. Knowing that for high traffic volumes and a high percentage of heavy vehicles, rigid pavement is more suitable compared to flexible pavement. In Baghdad, some highways consist of flexible pavement and others of combined pavement (flexible segments and rigid segments), so the study of the effect of surface type on traffic noise becomes an important matter. This study selected three highways: one with flexible pavement and two with the combined pavement. The results showed that the traffic noise generated by traffic on rigid pavement generates more noise than traffic on flexible pavement by about 2 dBA. A prediction model was generated to predict traffic noise depending on five variables (vehicle speed, traffic volume, skid number, distance between the edge of the inner lane and the sound level meter, and surface type). The measured traffic noise levels ranged from 73.23 to 82.86 dBA, which exceeded the permitted limits compared to the permissible Iraqi standards.